Seismic Performance and Mechanical Mechanism of Steel-Enhanced Damping Concrete Core Wall with Concealed Steel Plate Bracings under Oblique Loading - Zhangqi Hu; Taohua Chen; Mengfu Wang; Weirong Lu; Ran He (Advances in Civil Engineering)
This article focuses on the seismic performance and mechanical mechanisms of core walls under biaxial earthquakes. Through the oblique loading test (biaxial loading test) on one 1/6 scale steel-enhanced damping concrete core wall with steel plate bracings, the failure patterns, the load-bearing capacities, the yield mechanisms, and the strain distributions, etc. were investigated. Comparisons were made with the available test results of the authors’ previously unidirectional tested core walls and the tests completed by other scholars. The oblique tested core walls exhibited lower initial stiffness, but higher yield displacements, loading capacities, and ultimate displacements. A much more serious damage was also found in the wall limbs of oblique tested core walls by comparing with the unidirectional test core walls. Then finite element analysis (FEA) was also carried out to study the axial compression ratio (n), coupling beam span-depth ratio (l/h) on the stress distributions, and effective width of the end wall limbs (be). From the analysis results, it can be indicated that l/h affects much the stress distributions of oblique test core wall, which would be in eccentric force states if the coupling beam span-depth ratio was small, while the axial compression ratio does not affect the stress distributions dramatically. be varies with loading steps, the minimum value (be, min) of which increases with the decrease of l/h, and be, min will grow along with n.